Training for English Teachers on Writing Scientific Articles and Using Mendeley as a Collaboration and Reference Tool - Fiftinova Fiftinova; Erlina Erlina; Ismail Petrus; Muslih Hambali (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Writing scientific articles is a skill that must be owned by a teacher and the usage of Mendeley technology in writing scientific articles is a supporting facility in obtaining qualified scientific papers. Therefore, the execution of training activities needs to be carried out with the purpose of enhancing the motivation, knowledge, and abilities of high school English instructors in the city of Palembang. The activity model carried out is mentoring with the lecture approach, discussion, peer and tutor feedback and assignments. Evaluation of activities is carried out by administering tests and questionnaires as well as monitoring and documenting articles produced by the teacher. The findings of the evaluation demonstrated that the enthusiasm, knowledge, and skills of teacher participants in writing scientific articles increased. However, teachers still have issues using Mendeley as a citation and collaborative tool.